Altered functional connectivity in lesional peduncular hallucinosis with REM sleep behavior disorder. (January 2016) - Geddes, Maiya R.; Tie, Yanmei; Gabrieli, John D.E.; McGinnis, Scott M.; Golby, Alexandra J.; Whitfield-Gabrieli, Susan
Abstract: Brainstem lesions causing peduncular hallucinosis (PH) produce vivid visual hallucinations occasionally accompanied by sleep disorders. Overlapping brainstem regions modulate visual pathways and REM sleep functions via gating of thalamocortical networks. A 66-year-old man with paroxysmal atrial fibrillation developed abrupt–onset complex visual hallucinations with preserved insight and violent dream enactment behavior. Brain MRI showed restricted diffusion in the left rostrodorsal pons suggestive of an acute ischemic stroke. REM sleep behavior disorder (RBD) was diagnosed on polysomnography. We investigated the integrity of ponto-geniculate-occipital circuits with seed-based resting-state functional connectivity MRI (rs-fcMRI) in this patient compared to 46 controls. Rs-fcMRI revealed significantly reduced functional connectivity between the lesion and lateral geniculate nuclei (LGN), and between LGN and visual association cortex compared to controls. Conversely, functional connectivity between brainstem and visual association cortex, and between visual association cortex and prefrontal cortex (PFC) was significantly increased in the patient. Focal damage to the rostrodorsal pons is sufficient to cause RBD and PH in humans, suggesting an overlapping mechanism in both syndromes. This lesion produced a pattern of altered functional connectivity consistent with disrupted visual cortex connectivity via de-afferentation of thalamocortical pathways.